Pengaruh Static Exercise Otot Quadriceps femoris Terhadap Aktifitas Fungsional Sendi Lutut akibat Osteoarthritis - Setyawan, Muhammad Ghilang Maulud, Maskun Pudjianto, S.MPh, M.Kes, Dwi Rosella K, S.Fis.,Ftr.,M.Fis (2015)
Background: Osteoatrhitis is an inflammation of joints that marked with joint swelling , a reddish color , heat , pain and disruption of the motion , one of the problems it was often experienced is pain .Psychotherapy interference used to reduce pain is static exercise femoris quadriceps muscle .Static exercise training is static exercise or dynamic with repeated use of force , power and resilience. The Objective of Research: : To know the influence of static exercise femoris quadriceps muscle on the knee joint functional activity due to osteoarthritis. The Method of Research: kind of this research is an experimental quasi ( experiment specious and adopting a method of research single-case research with a design that analytic descriptive in therapy to 4 of respondents who meet the criteria for inclusion .Research is done in Posyandu Mawar Indah Pabelan Kartasura. An analysis of the results on this research is describing the results from t1 until t12 described in the table and graphs. Result of the Research: a decrease in pain osteoatrhitis the knee used womac index .In each sample is on respondents mrs Sm 0.041 % , mrs Tm 0.026 % , mrs Hn 0.038 % , and mrs Ss 0.047 % . Conclusion: The exercise that static qudriceps femoris provide positive effect for the reduction of pain osteoarthritis knee. Keywords: static exercise, osteoarthritis